PENANGANAN ANAK TERLANTAR MELALUI PANTI SOSIAL ASUHAN ANAK (PSAA) DI JAWA TENGAH - Hadi Karyono (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
Childcare Institutions as the vanguard of the state in carrying out state duties as instructed dalamn Constitution of the Republic of Indonesia Year 1945 section 34 subsection (1)